Widespread Recurrent Evolution of Genomic Features - Maeso, Ignacio (Oxford University Press, 2012)
The recent explosion of genome sequences from all major phylogenetic groups has unveiled an unexpected wealth of cases of recurrent evolution of strikingly similar genomic features in different lineages. Here, we review the diverse known types of recurrent evolution in eukaryotic genomes, with a special focus on metazoans, ranging from reductive genome evolution to origins of splice-leader trans-splicing, from tandem exon duplications to gene family expansions. We first propose a general classification scheme for evolutionary recurrence at the genomic level, based on the type of driving force—mutation or selection—and the environmental and genomic circumstances underlying these forces. We then discuss various cases of recurrent genomic evolution under this scheme. Finally, we provide a broader context for repeated genomic evolution, including the unique relationship of genomic recurrence with the genotype–phenotype map, and the ways in which the study of recurrent genomic evolution can be used to understand fundamental evolutionary processes.